2022
DOI: 10.1186/s12877-022-02757-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Z-substances in the management of insomnia in older adults: a systematic review for the development of recommendations to reduce potentially inappropriate prescribing

Abstract: Background Z-drugs are usually prescribed as first line pharmacological therapy for insomnia. However, the benefits and risks of Z-drugs may differ for older adults. This systematic review investigated the available evidence on the efficacy and safety of Z-drugs in the management of insomnia in older adults. Methods The Cochrane database of Systematic Reviews, the Cochrane Central Register of Controlled Trials, PubMed/MEDLINE and EMBASE were search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 58 publications
(161 reference statements)
0
13
0
Order By: Relevance
“…Zopiclone was another commonly used medicine in patients with a history of recent falls or prior history of use for over 4 weeks. Central nervous system (CNS) depressants, particularly those associated with a high risk of falls, are common PIMs in older adults, particularly in the oldest old group, 4,6 and can increase the risk of falls in this vulnerable population 14 …”
Section: Discussionmentioning
confidence: 99%
“…Zopiclone was another commonly used medicine in patients with a history of recent falls or prior history of use for over 4 weeks. Central nervous system (CNS) depressants, particularly those associated with a high risk of falls, are common PIMs in older adults, particularly in the oldest old group, 4,6 and can increase the risk of falls in this vulnerable population 14 …”
Section: Discussionmentioning
confidence: 99%
“…First, no ideal comparator to off-label, low-dose quetiapine exists, as other antipsychotics have at least some risk of cardiometa-bolic adverse events and are not used for the same indication as quetiapine, especially outside psychiatry. Z-drugs were chosen as the primary comparator, as they are a common alternative to low-dose quetiapine use as hypnotics 20 . However, Z-drug users are not an ideal comparator, likely having more comorbidities (especially in long-term users) than the average low-dose quetiapine user.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a new‐user, active‐comparator cohort study based on data from Danish nationwide health care registers. We included initiators of benzodiazepine‐related drugs (Z‐drugs) as an active comparator, because this drug class is widely used for the treatment of insomnia 20 . In sensitivity analyses, we also used SSRIs as an active comparator, which are used to treat anxiety, the second off‐label indication for low‐dose quetiapine.…”
Section: Methodsmentioning
confidence: 99%
“…59 On the other hand, a systematic review advises against using Z-drugs, for treating insomnia, despite its benefit in lengthening sleep, primarily due to the significant risk of fractures. 60 Melatonin used exogenously has positive impacts on cardiovascular health and improves the quality of sleep in patients with insomnia. 61 Another study demonstrated that 8 weeks, oral, 3 g…”
Section: Treatment Approachesmentioning
confidence: 99%
“…By speeding the beginning of sleep, increasing its efficiency, and lengthening the total time, dual and selective orexin‐2 receptor antagonists have demonstrated effectiveness in causing sleep in patients with insomnia disorders 59 . On the other hand, a systematic review advises against using Z‐drugs, for treating insomnia, despite its benefit in lengthening sleep, primarily due to the significant risk of fractures 60 …”
Section: Treatment Approachesmentioning
confidence: 99%